Organic silicon defoaming composition and preparation method thereof

By using polyether modified silicon oil, hydrophobic gas phase silicon dioxide, nanoccal carbonate and other components of organic silicon foam compositions, the existing removing bubbles are expressed in terms of foaming, bubbling, and compatibility The poor problem achieves better bubble effects and durability, and shows good compatibility in various industrial systems.

CN119345757AInactive Publication Date: 2025-01-24范丽芳
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411780924.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing silicone defoamers have poor performance in defoamability, foam inhibition and compatibility, resulting in limited application in many industrial scenarios.

Method used

A silicon foam composition, including polyether modified silicon oil, hydrophobic gas phase silicon dioxide, nano -carbonate, emulsifier, thickener, and deodorization water. And synergy.

Benefits of technology

It significantly improves the performance of the foam and the durability of bubbles, enhances compatibility, and ensures that the viscosity changes in the water and oily system are small and have no obvious abnormalities. It is suitable for a variety of industrial systems, which overcomes the routine combinations and are easy to layered and turbid. The problem of great changes in viscosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345757A_ABST
    Figure CN119345757A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fine chemical engineering preparations, and provides an organic silicon defoaming composition and a preparation method thereof, the organic silicon defoaming composition comprises the following components by weight: polydimethylsiloxane, trimethylchlorosilane, polyether modified silicone oil, an emulsifier, a cross-linking agent and a catalyst; the composition has better defoaming performance, foam inhibition durability and compatibility, effectively maintains production stability, reduces quality risk, has small viscosity change and no obvious abnormity in water-based and oil-based systems, is suitable for various industrial systems, and overcomes the defects of easy layering, turbidity, great viscosity change and the like of conventional compositions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fine chemical preparations, in particular to an organosilicon defoaming composition and a preparation method thereof. Background Art

[0002] In many industrial production fields, such as chemicals, papermaking, printing and dyeing, and coatings, foam has always been one of the key factors that plague the production process; the generation of foam will not only reduce production efficiency and extend the production cycle, but may also have a serious negative impact on product quality. For example, in chemical production, excessive foam may cause the liquid level in the reaction container to be artificially high, making it impossible to accurately control the chemical reaction, and even causing safety accidents such as overflow; in the papermaking industry, foam will cause holes, spots and other defects on the surface of the paper, reducing the strength and flatness of the paper; in the coating production process, foam will affect the coating performance of the coating, resulting in uneven coating thickness, reduced gloss and adhesion, and other problems.

[0003] Conventional silicone defoamers can only reduce foam height by about 60% within 10 seconds, and there is still a lot of foam residue after 60 seconds. The durability and compatibility of anti-foaming agents are relatively general, which limits their application in various industrial scenarios.

[0004] To this end, those skilled in the art have proposed an organosilicon defoaming composition and a preparation method thereof to solve the problems raised by the background art. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an organosilicon defoaming composition and a preparation method thereof, so as to solve the relatively general problems of defoaming property, foam suppression property and compatibility of conventional organosilicon defoamers in the prior art.

[0006] An organosilicon defoaming composition comprises the following components in parts by weight:

[0007] 30-60 parts of polyether modified silicone oil, 5-15 parts of hydrophobic fumed silica, 3-8 parts of nano calcium carbonate, 3-10 parts of emulsifier, 1-3 parts of thickener, 15-30 parts of deionized water;

[0008] The polyether modified silicone oil structural formula is:

[0009] Where R 1 and R 2 is methyl (CH3), x represents the main chain of organic silicon The degree of polymerization of the unit; R 3 It is a polyether segment, which is composed of polyoxyethylene (-(OCH2CH2) m -) and polyoxypropylene (-(OCH2CH(CH3)) n-) units, and the ratio of oxyethylene units to oxypropylene units is 3:7-7:3, the molecular weight is 1000-3000, y represents -(R containing a polyether segment 3 O) y The number of SiO units, z, represents the degree of polymerization of the siloxane units containing the polyether segments in the entire molecule.

[0010] Preferably, the hydrophobic fumed silica is mainly composed of silicon dioxide, which has been subjected to a surface hydrophobicization treatment using hexamethyldisilazane.

[0011] Preferably, the main component of the nano calcium carbonate is calcium carbonate (CaCO 3), After stearic acid (C 17 H 35 COOH) surface modification treatment.

[0012] Preferably, the emulsifier is polyoxyethylene sorbitan Monooleate, the structure is [C6H8O(CH2CH2O) a ] b OC 17 H 33 , where a represents the degree of polymerization of the polyoxyethylene chain segment and b represents the coefficient related to the degree of polymerization.

[0013] Preferably, the thickener is sodium carboxymethyl cellulose, the structure of which is shown as C6H7O2(OH) x (OCH2COONa) y ] n , where x+y=3, n represents the degree of polymerization.

[0014] A method for preparing an organosilicon defoaming composition comprises the following steps:

[0015] S1. Preparation of modified polyether modified silicone oil: add polyether and hydrogen-containing silicone oil in a three-necked flask with a stirrer, a thermometer and a reflux condenser at a molar ratio of 1.1-1.3:1, and then add 0.05% to 0.1% of the total mass of polyether and hydrogen-containing silicone oil in isopropanol chloroplatinic acid as a catalyst; protect with nitrogen, slowly heat to 80-100°C, and stir at this temperature for 3-5 hours; monitor the progress of the hydrosilylation reaction by infrared spectroscopy during the reaction, and when the concentration is between 2100-2200cm -1 When the Si-H bond stretching vibration peak at disappears, it indicates that the reaction is basically completed, and the modified polyether-modified silicone oil is obtained, which is cooled to room temperature for use;

[0016] S2, pretreatment of hydrophobic silica, adding hydrophobic fumed silica to an appropriate amount of anhydrous ethanol, ultrasonically dispersing in an ultrasonic disperser for 30 to 60 minutes, so that the silica is evenly dispersed in the ethanol; adding hexamethyldisilazane accounting for 5% to 10% of the mass of the hydrophobic fumed silica, stirring and reflux at 60-80°C for 2-3 hours, after the reaction is completed, removing ethanol by reduced pressure distillation to obtain the pretreated hydrophobic fumed silica, drying in a vacuum drying oven to constant weight, and set aside;

[0017] S3, pretreatment of nano calcium carbonate, adding nano calcium carbonate to an appropriate amount of toluene solution, forming a suspension under high-speed stirring, then slowly dropping a toluene solution of stearic acid accounting for 3% to 5% of the mass of the nano calcium carbonate, stirring and reacting at 80-100° C. for 1-2 hours; after the reaction, centrifugally separating to obtain the modified nano calcium carbonate, washing with toluene 2-3 times, and drying in a vacuum drying oven to constant weight for standby use;

[0018] S4, preparation of the defoaming composition, adding deionized water into the kettle of a high-speed dispersing emulsifier, starting stirring, adding an emulsifier and a thickener in sequence under low-speed stirring, and stirring until they are completely dissolved and uniform; slowly adding the pretreated hydrophobic fumed silica and nano-calcium carbonate into the kettle, increasing the stirring speed to 1000-1500r / min, stirring for 30-60 minutes, so that the solid particles are fully dispersed and uniform; finally, slowly adding the modified polyether-modified silicone oil dropwise into the kettle, after the addition is completed, increasing the stirring speed to 2000-3000r / min, and continuing stirring for 1-2 hours to obtain a uniform and stable organosilicon defoaming composition.

[0019] Preferably, deionized water is added into the kettle of the high-speed dispersing emulsifier, and the low-speed stirring speed is 300-500 r / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The composition has better defoaming performance, foam suppression durability and compatibility, effectively maintains production stability, reduces quality risks, has little viscosity change and no obvious abnormality in aqueous and oily systems, is suitable for a variety of industrial systems, and overcomes the defects of conventional compositions such as easy stratification, turbidity and large viscosity changes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the process of this method. DETAILED DESCRIPTION

[0023] The following is a further detailed description of the embodiments of the present invention in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0024] As attached Figure 1 As shown: The present invention provides an organosilicon defoaming composition, comprising the following components in parts by weight:

[0025] 30-60 parts of polyether modified silicone oil, 5-15 parts of hydrophobic fumed silica, 3-8 parts of nano calcium carbonate, 3-10 parts of emulsifier, 1-3 parts of thickener, 15-30 parts of deionized water;

[0026] The structural formula of polyether modified silicone oil is:

[0027] Where R 1 and R 2 is methyl (CH3), x represents the main chain of organic silicon The degree of polymerization of the unit; R 3 It is a polyether segment, which is composed of polyoxyethylene (-(OCH2CH2) m -) and polyoxypropylene (-(OCH2CH(CH3)) n -) units, and the ratio of oxyethylene units to oxypropylene units is 3:7-7:3, the molecular weight is 1000-3000, y represents -(R containing a polyether segment 3 O) y The number of SiO units, z, represents the degree of polymerization of the siloxane units containing the polyether segments in the entire molecule.

[0028] 5-15 parts of hydrophobic fumed silica: The main component of hydrophobic fumed silica is silicon dioxide SiO2, which is treated with hexamethyldisilazane (CH 3)3 The surface of SiNHSi(CH3)3 is hydrophobized. After the treatment, its surface will be partially covered with hydrophobic groups such as silylmethyl Si(CH3)3, but the overall core structure is still silicon dioxide.

[0029] 3-8 parts of nano calcium carbonate: The main component of nano calcium carbonate is calcium carbonate (CaCO 3), After stearic acid (C 17 H 35 COOH) surface modification, the surface will have stearate ions (C 17 H 35 COO -) Combined with calcium carbonate particles, it changes its surface properties, enhances the interaction with other components and the dispersibility in the system.

[0030] Emulsifier 3-10 parts: Emulsifier is polyoxyethylene sorbitan Monooleate (Tween-80), the structure is [C6H8O(CH2CH2O) a ] b OC 17 H 33, where a represents the degree of polymerization of the polyoxyethylene chain segment and b represents the coefficient related to the degree of polymerization.

[0031] Thickener 1-3 parts: The thickener is sodium carboxymethyl cellulose, the structure of which is [C6H7O2(OH) x (OCH2COONa) y ] n , where x+y=3, n represents the degree of polymerization; its structure is the product of partial hydroxyl groups (-OH) on the cellulose molecular chain being replaced by carboxymethyl groups (-CH2COONa).

[0032] The preparation steps are as follows:

[0033] S1. Add polyether and hydrogen-containing silicone oil in a three-necked flask with a stirrer, a thermometer and a reflux condenser in a molar ratio of 1.1-1.3:1, and then add 0.05% to 0.1% of the total mass of polyether and hydrogen-containing silicone oil in isopropanol chloroplatinic acid as a catalyst; protect with nitrogen, slowly heat to 80-100°C, and stir at this temperature for 3-5 hours; monitor the progress of the hydrosilylation reaction by infrared spectroscopy during the reaction. When the wavelength is between 2100-2200cm -1 When the SiH bond stretching vibration peak at the position disappears, it indicates that the reaction is basically completed, and the modified polyether modified silicone oil is obtained, which is cooled to room temperature for use.

[0034] S2. Add hydrophobic fumed silica to an appropriate amount of anhydrous ethanol, and ultrasonically disperse it in an ultrasonic disperser for 30 to 60 minutes to uniformly disperse the silica in the ethanol; add hexamethyldisilazane accounting for 5% to 10% of the mass of the hydrophobic fumed silica, and stir and reflux at 60-80°C for 2-3 hours. After the reaction is completed, remove the ethanol by reduced pressure distillation to obtain the pretreated hydrophobic fumed silica, and dry it in a vacuum drying oven to constant weight for standby use.

[0035] S3, adding nano calcium carbonate to an appropriate amount of toluene solution to form a suspension under high-speed stirring, then slowly dropping a toluene solution of stearic acid accounting for 3% to 5% of the mass of the nano calcium carbonate, stirring and reacting at 80-100° C. for 1-2 hours; after the reaction, centrifugally separating to obtain the modified nano calcium carbonate, washing with toluene 2-3 times, and drying in a vacuum drying oven to constant weight for standby use;

[0036] S4. Add deionized water into the kettle of the high-speed dispersing emulsifier, start stirring, add emulsifier and thickener in sequence at a low stirring speed of 300-500r / min, and stir until they are completely dissolved and uniform; slowly add the pretreated hydrophobic fumed silica and nano calcium carbonate into the kettle, increase the stirring speed to 1000-1500r / min, and stir for 30-60 minutes to fully disperse the solid particles; finally, slowly add the modified polyether-modified silicone oil into the kettle, and after the addition is completed, increase the stirring speed to 2000-3000r / min, and continue stirring for 1-2 hours to obtain a uniform and stable silicone defoaming composition.

[0037] Embodiment 1:

[0038] Preparation of modified polyether modified silicone oil: 45g of polyoxyethylene-polyoxypropylene ether with a molecular weight of 1500 and a ratio of oxyethylene units to oxypropylene units of 4:6 and 30g of hydrogen-containing silicone oil with a hydrogen content of 0.2% were weighed and added into a three-necked flask, and then 0.07g of chloroplatinic acid isopropanol solution was added. Under nitrogen protection, the temperature was raised to 90°C and stirred for reaction for 4 hours to obtain modified polyether modified silicone oil.

[0039] Pretreatment of hydrophobic silica: 10 g of hydrophobic fumed silica was added to 50 ml of anhydrous ethanol and ultrasonically dispersed for 45 minutes. 0.7 g of hexamethyldisilazane was added and stirred and refluxed at 70°C for 2.5 hours. The ethanol was removed by vacuum distillation and the mixture was dried to constant weight.

[0040] Pretreatment of nano calcium carbonate: Take 5g of nano calcium carbonate and add it to 30ml of toluene solution, stir at high speed to form a suspension. Add 0.2g of stearic acid in toluene solution dropwise, stir and react at 90℃ for 1.5 hours. Centrifuge, wash with toluene 3 times, and vacuum dry to constant weight.

[0041] Preparation of defoaming composition: Add 20g of deionized water into the kettle of a high-speed dispersing emulsifier, add 5g of an emulsifier mixture of Tween 80 and sodium dodecylbenzene sulfonate with a mass ratio of 2.5:1 and 2g of sodium carboxymethyl cellulose under stirring at 400r / min, and stir until uniformly dissolved. Add pretreated hydrophobic fumed silica and nano calcium carbonate, increase the stirring speed to 1200r / min, and stir for 45 minutes. Slowly drop the modified polyether-modified silicone oil, and after the dropwise addition is completed, increase the stirring speed to 2500r / min, stir for 1.5 hours, and obtain the organosilicon defoaming composition.

[0042] Example 2

[0043] Preparation of modified polyether-modified silicone oil: Weigh 50 g of polyoxyethylene-polyoxypropylene ether with a molecular weight of 2000 and a ratio of oxyethylene units to oxypropylene units of 5:5 and 35 g of hydrogen-containing silicone oil with a hydrogen content of 0.15% and add them into a three-necked flask, and then add 0.08 g of chloroplatinic acid isopropanol solution; under nitrogen protection, heat to 85°C, stir and react for 4.5 hours to obtain modified polyether-modified silicone oil.

[0044] Pretreatment of hydrophobic silica: 12 g of hydrophobic fumed silica was added to 60 ml of anhydrous ethanol and ultrasonically dispersed for 50 minutes; 0.9 g of hexamethyldisilazane was added, stirred and refluxed at 75° C. for 2 hours, ethanol was removed by vacuum distillation, and vacuum dried to constant weight.

[0045] Pretreatment of nano calcium carbonate: 6 g of nano calcium carbonate was added to 35 ml of toluene solution, and stirred at high speed to form a suspension; 0.25 g of stearic acid in toluene solution was added dropwise, and stirred at 95°C for 1 hour. Centrifugal separation was performed, and toluene was washed twice, and vacuum dried to constant weight.

[0046] Preparation of the defoaming composition: 25g of deionized water is added to the kettle of a high-speed dispersing emulsifier, and 6g of an emulsifier mixture of Tween 80 and sodium dodecylbenzene sulfonate in a mass ratio of 3:1 and 2.5g of sodium carboxymethyl cellulose are added under stirring at 350r / min, and stirred until uniformly dissolved; pre-treated hydrophobic fumed silica and nano calcium carbonate are added, and the stirring speed is increased to 1300r / min, and stirred for 50 minutes. Modified polyether-modified silicone oil is slowly added dropwise, and after the addition is completed, the stirring speed is increased to 2800r / min, and stirred for 1 hour to obtain an organosilicon defoaming composition.

[0047] Example 3

[0048] Preparation of modified polyether modified silicone oil: Weigh 55 g of polyoxyethylene-polyoxypropylene ether with a molecular weight of 2500 and a ratio of oxyethylene units to oxypropylene units of 6:4 and 40 g of hydrogen-containing silicone oil with a hydrogen content of 0.1% and add them into a three-necked flask, and then add 0.09 g of chloroplatinic acid isopropanol solution; under nitrogen protection, heat to 95°C, stir and react for 3.5 hours to obtain modified polyether modified silicone oil.

[0049] Pretreatment of hydrophobic silica: 15 g of hydrophobic fumed silica was added to 70 ml of anhydrous ethanol and ultrasonically dispersed for 35 minutes; 1.2 g of hexamethyldisilazane was added, stirred and refluxed at 65° C. for 3 hours, ethanol was removed by vacuum distillation, and vacuum dried to constant weight.

[0050] Pretreatment of nano-calcium carbonate: Take 8g of nano-calcium carbonate and add it to 40ml of toluene solution, stir at high speed to form a suspension; add 0.35g of stearic acid toluene solution dropwise, stir and react at 85°C for 2 hours; centrifuge, wash with toluene 3 times, and vacuum dry to constant weight.

[0051] Preparation of a defoaming composition: 30 g of deionized water is added into a kettle of a high-speed dispersing emulsifier, 8 g of an emulsifier mixture of Tween 80 and sodium dodecylbenzene sulfonate in a mass ratio of 2:1 and 3 g of sodium carboxymethyl cellulose are added under stirring at 450 r / min, and stirred until uniformly dissolved; pretreated hydrophobic fumed silica and nano calcium carbonate are added, the stirring speed is increased to 1400 r / min, and the mixture is stirred for 35 minutes; modified polyether-modified silicone oil is slowly added dropwise, and after the addition is completed, the stirring speed is increased to 2200 r / min, and the mixture is stirred for 2 hours to obtain an organosilicon defoaming composition.

[0052] Comparative Example:

[0053] A simple organosilicon defoamer is prepared according to a conventional method, which consists of only 30 parts of dimethyl silicone oil (viscosity of 500 cs), 10 parts of ordinary fumed silica (not specially hydrophobized), 5 parts of a single non-ionic emulsifier Tween 80 and 55 parts of deionized water. The preparation method is as follows: after the dimethyl silicone oil and the fumed silica are mixed and ground evenly, they are added into deionized water containing the emulsifier, and emulsified and dispersed under high-speed stirring to obtain the defoamer.

[0054] Defoaming performance test:

[0055] Example 1: After adding 0.1 ml of the defoaming composition prepared in Example 1 to 50 ml of a 0.5% aqueous solution of sodium dodecylbenzene sulfonate and shaking for 30 seconds, the foam height was 180 mm at 0 seconds. At 5 seconds, the foam height dropped rapidly to 20 mm, and the foam height reduction rate reached 88.9%. At 10 seconds, the foam height was only 15 mm, and the reduction rate was as high as 91.7%. At 30 seconds, the foam height was further reduced to 8 mm, and at 60 seconds, the foam was almost completely eliminated, with only tiny foam of about 2 mm remaining.

[0056] Example 2: For the defoaming composition of Example 2, the initial foam height is also about 180 mm. At 5 seconds, the foam height drops to 18 mm, with a reduction rate of 90%; at 10 seconds, the foam height is 12 mm, with a reduction rate of 93.3%. At 30 seconds, the foam height is 6 mm, and at 60 seconds, the foam completely disappears, with a foam height of 0 mm.

[0057] Example 3: In Example 3, the foam height at 0 seconds was about 185 mm, and at 5 seconds the foam height dropped to 16 mm, a reduction rate of about 91.4%; at 10 seconds it was 10 mm, a reduction rate of about 94.6%. At 30 seconds, the foam height was 5 mm, and at 60 seconds, the foam was completely eliminated.

[0058] Comparative Example: The foam height of the comparative example was also around 180mm at 0 seconds. At 5 seconds, the foam height only dropped to 100mm, with a reduction rate of 44.4%; at 10 seconds, the foam height was 72mm, with a reduction rate of 60%. At 30 seconds, the foam height was still 35mm, and at 60 seconds, the foam height was still around 15mm, with obvious foam residue.

[0059] Antifoaming performance test:

[0060] Example 1: The test was carried out in a 100 ml stoppered measuring cylinder, and 0.2 ml of the defoaming composition of Example 1 was added. After oscillation for 60 seconds and then allowed to stand, the foam height was 3 ml at 1 minute, 2 ml at 2 minutes, 1.5 ml at 3 minutes, 1 ml at 4 minutes, and 0.5 ml at 5 minutes, with almost no new foam generated.

[0061] Example 2: When the defoaming composition of Example 2 was tested, the foam height was 2.5 ml at 1 minute; 1.8 ml at 2 minutes; 1.2 ml at 3 minutes; 0.8 ml at 4 minutes; and 0.3 ml at 5 minutes, and the foam suppression effect was significant.

[0062] Example 3: For Example 3, the foam height is 2 ml at 1 minute; at 2 minutes, the foam height is 1.5 ml; at 3 minutes, the foam height is 1 ml; at 4 minutes, the foam height is 0.6 ml; at 5 minutes, the foam height is 0.2 ml, which can effectively inhibit the re-generation of foam.

[0063] Comparative example: In the comparative example, the foam height reaches 15 ml at 1 minute; at 2 minutes, the foam height is 18 ml; at 3 minutes, the foam height is 20 ml; at 4 minutes, the foam height is 22 ml; at 5 minutes, the foam height continues to rise to about 25 ml, and the foam regeneration situation is serious.

[0064] Compatibility test:

[0065] Example 1: In water-based acrylic paint, before adding the defoaming composition, the initial viscosity of the paint was 800mPa·s. After adding the defoaming composition of Example 1, the viscosity became 830mPa·s, the viscosity change rate was about 3.75%, and the system had a uniform appearance without stratification or turbidity. In oil-based polyurethane paint, after adding, the viscosity changed from 1200mPa·s to 1320mPa·s, the change rate was about 10%, there was slight turbidity but it did not affect the coating and use performance. In papermaking white water, the initial viscosity was 3mPa·s, after adding, it became 3.15mPa·s, the change rate was about 5%, and the system was clear and transparent.

[0066] Example 2: For water-based acrylic paint, the initial viscosity is 850mPa·s. After adding the defoaming composition of Example 2, the viscosity becomes 880mPa·s, with a change rate of about 3.53%, and no abnormal phenomenon. In oil-based polyurethane paint, the initial viscosity is 1150mPa·s, and after adding, it becomes 1250mPa·s, with a change rate of about 8.7%, and it is slightly turbid. The initial viscosity of papermaking white water is 2.8mPa·s, and after adding, it becomes 2.95mPa·s, with a change rate of about 5.36%, and the compatibility is good.

[0067] Example 3: In water-based acrylic paint, the initial viscosity is 900mPa·s. After adding the defoaming composition of Example 3, the viscosity becomes 935mPa·s, with a change rate of about 3.89%, and the system is stable. The initial viscosity of oily polyurethane paint is 1300mPa·s, which becomes 1420mPa·s after adding, with a change rate of about 9.23%, and slightly turbid. The initial viscosity of papermaking white water is 3.2mPa·s, which becomes 3.35mPa·s after adding, with a change rate of about 4.69%, and there is no stratification and turbidity.

[0068] Comparative Example: In water-based acrylic paint, the initial viscosity is 750mPa·s. After adding the defoaming composition of the comparative example, the viscosity becomes 862.5mPa·s, with a change rate of about 15%, and a small amount of stratification occurs. In oil-based polyurethane paint, the initial viscosity is 1000mPa·s. After adding, severe stratification occurs, and the viscosity change cannot be accurately measured, and the paint cannot be used normally. The initial viscosity of papermaking white water is 3.5mPa·s. After adding, it becomes 4.025mPa·s, with a change rate of about 15%, with slight turbidity and a small amount of precipitation.

[0069] Through the above detailed data comparison, it can be more intuitively seen that the organosilicon defoaming composition of the present invention has significant advantages over traditional organosilicon defoamers in terms of defoaming performance, foam suppression performance and compatibility.

[0070] In terms of defoaming performance, thanks to the special structure of the modified polyether-modified silicone oil, the appropriate amount of polyether segments introduced into its molecular chain can effectively improve the compatibility and dispersibility in the aqueous system, so that it can quickly spread on the foam surface. For example, in the experiment, the defoaming composition prepared in Examples 1-3 has a foam height reduction rate of more than 90% within 10 seconds, and the foam is basically eliminated in 60 seconds. Compared with the conventional composition in the same time, the defoaming effect has been greatly improved, and it can quickly deal with the foam generated in various industrial production processes, significantly improving production efficiency.

[0071] In terms of foam suppression and persistence, the components work synergistically, the hydrophobic fumed silica forms a stable hydrophobic barrier on the foam surface, and the nano-calcium carbonate enhances the thixotropy of the composition and helps maintain the overall stability, making it difficult for foam to regenerate. The height of the foam regenerated by the defoaming composition of Examples 1-3 within 5 minutes is less than 5 ml, which is much better than the conventional composition, can effectively reduce the repeated occurrence of foam, ensure the continuity and stability of the production process, and reduce the risk of product quality fluctuations caused by foam regeneration.

[0072] In terms of compatibility, a mixture of nonionic emulsifier Tween 80 and anionic emulsifier sodium dodecylbenzene sulfonate in a specific mass ratio is selected as an emulsifier, combined with sodium carboxymethyl cellulose as a thickener and deionized water as a dispersion medium to make the components evenly dispersed. It has good compatibility in water-based paints and papermaking white water, with no obvious changes in the system and a viscosity change rate of less than 5%; although there is slight turbidity in oil-based paints, it does not affect the use, and the viscosity change rate is within 10%, overcoming the problems of conventional compositions being prone to stratification, turbidity, and large viscosity changes in different systems, so that it can be widely used in the defoaming needs of various industrial systems, expanding the scope of application of defoamers, and reducing the cost and technical difficulty of enterprises frequently replacing defoamers due to the use of different systems.

[0073] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. An organosilicon defoaming composition, characterized in that: The composition comprises the following components in parts by weight: 30-60 parts of polyether modified silicone oil, 5-15 parts of hydrophobic fumed silica, 3-8 parts of nano calcium carbonate, 3-10 parts of emulsifier, 1-3 parts of thickener, 15-30 parts of deionized water; The polyether modified silicone oil structural formula is: Where R 1 and R 2 is methyl (CH3), x represents the main chain of organic silicon The degree of polymerization of the unit; R 3 It is a polyether segment, which is composed of polyoxyethylene (-(OCH2CH2) m -) and polyoxypropylene (-(OCH2CH(CH3)) n -) units, and the ratio of oxyethylene units to oxypropylene units is 3:7-7:3, the molecular weight is 1000-3000, y represents -(R containing a polyether segment 3 O) y The number of SiO- units, z represents the degree of polymerization of the siloxane units containing the polyether chain segments in the whole molecule.

2. The organosilicon defoaming composition according to claim 1, characterized in that: The hydrophobic fumed silica is mainly composed of silicon dioxide, which is subjected to a surface hydrophobicization treatment using hexamethyldisilazane.

3. An organosilicon defoaming composition as claimed in claim 2, characterized in that: The main component of the nano calcium carbonate is calcium carbonate (CaCO3) , After stearic acid (C 17 H 35 COOH) surface modification treatment.

4. An organosilicon defoaming composition as claimed in claim 3, characterized in that: The emulsifier is polyoxyethylene sorbitan Monooleate, the structure is [C6H8O(CH2CH2O) a ] b OC 17 H 33 , where a represents the degree of polymerization of the polyoxyethylene chain segment and b represents the polymerization coefficient.

5. The organosilicon defoaming composition according to claim 4, characterized in that: The thickener is sodium carboxymethyl cellulose, and its structure is shown as [C6H7O2(OH) x (OCH2COONa) y ] n , where x+y=3, n represents the degree of polymerization.

6. A method for preparing an organosilicon defoaming composition, for preparing an organosilicon defoaming composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Preparation of modified polyether modified silicone oil: add polyether and hydrogen-containing silicone oil in a three-necked flask with a stirrer, a thermometer and a reflux condenser at a molar ratio of 1.1-1.3:1, and then add 0.05% to 0.1% of the total mass of polyether and hydrogen-containing silicone oil in isopropanol chloroplatinic acid as a catalyst; protect with nitrogen, slowly heat to 80-100°C, and stir at this temperature for 3-5 hours; monitor the progress of the hydrosilylation reaction by infrared spectroscopy during the reaction, and when the concentration is between 2100-2200cm -1 When the Si-H bond stretching vibration peak at disappears, it indicates that the reaction is basically completed, and the modified polyether-modified silicone oil is obtained, which is cooled to room temperature for use; S2, pretreatment of hydrophobic silica, adding hydrophobic fumed silica to anhydrous ethanol, ultrasonically dispersing in an ultrasonic disperser for 30 to 60 minutes; adding hexamethyldisilazane accounting for 5% to 10% of the mass of hydrophobic fumed silica, stirring and reflux at 60-80°C for 2-3 hours, after the reaction is completed, removing ethanol by reduced pressure distillation to obtain pretreated hydrophobic fumed silica, drying in a vacuum drying oven to constant weight, and set aside; S3, pretreatment of nano calcium carbonate, adding nano calcium carbonate to an appropriate amount of toluene solution, forming a suspension under high-speed stirring, then dripping a toluene solution of stearic acid accounting for 3% to 5% of the mass of the nano calcium carbonate, stirring and reacting at 80-100° C. for 1-2 hours; after the reaction, centrifugation is performed to obtain the modified nano calcium carbonate, washing it with toluene 2-3 times, and drying it in a vacuum drying oven to constant weight for standby use; S4, preparation of the defoaming composition, adding deionized water into the kettle of a high-speed dispersing emulsifier, starting stirring, adding an emulsifier and a thickener in sequence under low-speed stirring, and stirring until they are completely dissolved and uniform; adding the pretreated hydrophobic fumed silica and nano-calcium carbonate into the kettle, increasing the stirring speed to 1000-1500 r / min, and stirring for 30-60 minutes; finally, adding the modified polyether-modified silicone oil dropwise into the kettle, after the addition is completed, increasing the stirring speed to 2000-3000 r / min, and continuing stirring for 1-2 hours to obtain the organosilicon defoaming composition.

7. A method for preparing an organosilicon defoaming composition according to claim 6, characterized in that: Deionized water is added into the kettle of the high-speed dispersing emulsifier, and the low-speed stirring speed is 300-500r / min.

Citation Information

Cited By

  • Fluorine-containing surfactant low-surface tension defoaming agent and preparation method thereof

    CN120815365A